2008
DOI: 10.1123/jab.24.3.280
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Consistency of Propulsive Cycles and Maximum Angular Velocity during Wheelchair Racing

Abstract: The purposes of this study were to examine the consistency of wheelchair athletes’ upper-limb kinematics in consecutive propulsive cycles and to investigate the relationship between the maximum angular velocities of the upper arm and forearm and the consistency of the upper-limb kinematical pattern. Eleven elite international wheelchair racers propelled their own chairs on a roller while performing maximum speeds during wheelchair propulsion. A Qualisys motion analysis system was used to film the wheelchair pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Unsurprisingly, a number of studies [4,6,34,35] have indicated that many kinematic and kinetic measures increase with speed. For example, Wang, Vrongistinos, & Xu [34] found that over consecutive pushes during wheelchair sprinting, higher range of motion values occurred around the shoulder and elbow leading to greater maximum angular velocity of the upper arm and forearm and an increased range of motion over which angular acceleration could be produced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, a number of studies [4,6,34,35] have indicated that many kinematic and kinetic measures increase with speed. For example, Wang, Vrongistinos, & Xu [34] found that over consecutive pushes during wheelchair sprinting, higher range of motion values occurred around the shoulder and elbow leading to greater maximum angular velocity of the upper arm and forearm and an increased range of motion over which angular acceleration could be produced.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Wang, Vrongistinos, & Xu [34] found that over consecutive pushes during wheelchair sprinting, higher range of motion values occurred around the shoulder and elbow leading to greater maximum angular velocity of the upper arm and forearm and an increased range of motion over which angular acceleration could be produced. In comparing the speed and stroke cycle characteristics during the 100 m wheelchair race, Chow [35] also found significant differences in stroke speed, length, push and recovery times at different portions of the race.…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated that during consecutive cycles of wheelchair propulsion at maximum speed, the increased maximum angular velocity may lead to increased variability in the upper limb angular kinematics. 8 Masson et al obtained the speed and driving force measured from a roller system and used a video camera to derive push time and recovery time. Theoretical predictions of power transfer to the wheelchair were computed using a muscle-free Lagrangian dynamic model of the upper limb segments.…”
Section: Introductionmentioning
confidence: 99%
“…We speculated that the increased percentage time in the recovery phase would give the performer more percentage time for acceleration to speed up the hand velocity in the drive phase. 24,44 It is worth noting that the present study's participants were manual wheelchair users using recreational wheelchairs, while the participants in the study of Wang et al 24 were racing wheelchair athletes using racing wheelchairs. Therefore, regardless of the performers and wheelchair types, the propulsion ranges remained relatively constant as the speed increased.…”
Section: Hand Positions and Time In Drive Phase Recovery Phase And Pr...mentioning
confidence: 73%
“…The results of the linear velocities and accelerations of the upper extremity in the present study are consistent with the results of previous studies. 13,24,44…”
Section: Hand Positions and Time In Drive Phase Recovery Phase And Pr...mentioning
confidence: 99%